Evaluation of circadian rhythm and prognostic variability pre-and post-CEA or CAS treatment in patients with carotid artery stenosis - Quan, Yi; Wang, Zhongzhu; Zhang, Tao; Sui, Yanyong; Zhang, Xin; Ji, Xueliang; Liu, Ao-fei; Jiang, Weijian (Frontiers in Neurology, 2025)
ObjectiveCarotid artery stenosis, primarily caused by atherosclerosis, is a major risk factor for ischemic stroke. Carotid endarterectomy (CEA) and carotid artery stenting (CAS) are established interventions to reduce stroke risk and restore cerebral blood flow. However, the effect of these treatments on circadian rhythms, and their influence on stroke recovery, remains underexplored. This study aims to assess how disruptions in circadian rhythms—specifically sleep quality and blood pressure variability—impact recovery in patients undergoing CEA or CAS.MethodsWe conducted a prospective study involving 177 patients with carotid artery stenosis, all treated with either CEA or CAS. Patients were followed for 90 days post-treatment, with neurological outcomes evaluated using the NIHSS Stroke Scale (NIHSS). Circadian rhythm-related factors, including sleep quality (Pittsburgh Sleep Quality Index [PSQI]) and blood pressure variability (daytime systolic and nighttime diastolic BP), were assessed pre-and post-treatment. Stepwise regression was used to identify predictors of stroke recovery.ResultsIn a cohort of 177 patients with symptomatic carotid atherosclerotic stenosis, stepwise regression identified post-treatment changes in PSQI, nighttime diastolic blood pressure, and the presence of coronary heart disease as significant independent predictors of poor neurological outcomes (p < 0.001). Both CEA and CAS significantly improved daytime systolic (p < 0.01) and nighttime diastolic blood pressure (p < 0.01). Patients with poorer prognosis had higher post-treatment PSQI scores (p < 0.001). Additionally, increased physical activity after treatment was linked to improved neurological recovery.ConclusionThis study highlights the critical role of circadian rhythm regulation and cardiovascular health in stroke recovery following CEA or CAS. Stepwise regression analysis revealed that sleep quality, blood pressure stability, and coronary heart disease were key predictors of neurological outcomes, underscoring the importance of integrating circadian rhythm management into rehabilitation strategies. These results provide a robust scientific foundation for further investigation into the role of circadian rhythms in clinical practice.